Organización del área administrativa de la Federación Colombiana de Gestión Humana – ACRIP (2023)
The Colombian Federation of Human Management - ACRIP was founded 65 years ago, with the aim of supporting the development and improvement of human talent areas in Colombia, in addition to betting on the growth of companies and promoting their productivity. The present academic work is focused on organizing the administrative area of the Colombian Federation of Human Management - ACRIP that meets the need of the organization.